Magnetic particles for immunoassay and method for producing same

Magnetic particles with a crosslinked inorganic layer and a polymer layer addressing issues of iron elution, sensitivity, and dispersibility, significantly improve the performance of immunoassays by enhancing acid resistance, water dispersibility, and specific surface area.

JP7647055B2Active Publication Date: 2025-03-18TOSOH CORP
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2020169518
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-09
Filing Date
2020-10-07
Publication Date
2025-03-18
Estimated Expiration
2040-10-07

AI Technical Summary

Technical Problem

Existing magnetic particles for immunoassays suffer from iron elution in acidic aqueous solutions, reduced sensitivity due to non-specific adsorption, and limited dispersibility in water, which hinders their effectiveness in carrying physiologically active substances.

Method used

The development of magnetic particles with a crosslinked inorganic layer containing nanomagnetic materials and a polymer layer with polyethylene glycol and carboxyl group-containing structural units, enhancing acid resistance, dispersibility, and specific surface area.

Benefits of technology

The proposed magnetic particles effectively suppress iron elution, improve water dispersibility, reduce non-specific adsorption, and increase the specific surface area, leading to enhanced sensitivity and capacity to carry physiologically active substances in immunoassays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647055000002
    Figure 0007647055000002
  • Figure 0007647055000001
    Figure 0007647055000001
Patent Text Reader

Abstract

To provide a magnetic particle which has superior acid resistance that leads to less elution of iron even when treated with an acidic aqueous solution, exhibits good dispersibility to water, less non-specific absorption, and large specific particle surface area that allows for carrying a large amount of physiologically active substances, and is capable of enhancing immunoassay sensitivity.SOLUTION: A magnetic particle for antibody binding is provided comprising a core particle, a first coating layer formed on a surface of the core particle, and a second coating layer formed on a surface of the first coating layer. The first coating layer is a cross-linked inorganic layer containing nano magnetic materials. The second coating layer is a polymer layer having a polyethylene-glycol-group-containing structural unit and has a carboxyl-group-containing structural unit.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to magnetic particles for use in immunoassays and a method for producing the same. [Background technology]

[0002] Magnetic particles are used as carriers for carrying physiologically active substances for immunoassays, taking advantage of their magnetic properties. However, when binding physiologically active substances such as antibodies to the surface of magnetic particles, the reaction is carried out in an acidic aqueous solution, which causes problems such as the detachment of magnetic bodies and the elution of iron ions, which are derived from magnetic body components. Since iron acts as an interfering substance in immune reactions, there are problems such as a decrease in sensitivity of immune assays and a limitation in the number of physiologically active substances that can be sensitized, and magnetic particles with less leakage of such magnetic body components are desired. In addition, magnetic particles as carriers for immune assays are required to have low noise by suppressing nonspecific adsorption of components unrelated to immune reactions, and high signaling that allows many physiologically active substances to be carried, thereby enabling high sensitivity in immune assays. Furthermore, since magnetic particles are dispersed in an aqueous solution for use in immune assays, magnetic particles with good dispersibility in water are required.

[0003] To solve these problems, particles for immunoassays have been proposed in which the surface of a magnetic particle having a ferrite coating layer on the surface of the core particle is coated with an organic silane coupling agent having a functional group such as an amino group, and a carboxyl group is further introduced (see, for example, Patent Document 1). Also, particles for immunoassays have been proposed in which a nanomagnetic material coated with a hydrophobic organic silane coupling agent is adsorbed onto a core particle, and then the nanomagnetic material is coated with a hydrophobic polymer so that it is embedded, and a functional group is further introduced onto the surface (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 2979414 [Patent Document 2] Patent No. 3738847 Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, although the elution of iron can be suppressed by treating the surface with an organic silane coupling agent, there is a problem in that the suppression is insufficient.

[0006] In Patent Document 2, the elution of iron is suppressed by forming a hydrophobic polymer layer after coating the surface of a core particle with a magnetic material treated with a hydrophobic organic silane coupling agent, but there is a problem that the hydrophobic polymer layer deteriorates the dispersibility of the magnetic particles in water. In addition, since the nanomagnetic material is buried in the polymer by coating with a hydrophobic polymer layer, the specific surface area of ​​the magnetic particles is small, and a large amount of magnetic particles is required to support the desired amount of a physiologically active substance such as an antibody.

[0007] The present invention has been made in consideration of the above-mentioned problems, and aims to provide magnetic particles which have excellent acid resistance, cause little iron leaching even when treated with an acidic aqueous solution, have good dispersibility in water, have little non-specific adsorption, and have a large specific surface area for carrying a large amount of physiologically active substances, thereby enabling high sensitivity in immunoassays. [Means for solving the problem]

[0008] As a result of extensive research in light of the above, the inventors have discovered that the above problems can be solved by the following magnetic particles and method for producing magnetic particles, thereby completing the present invention.

[0009] The various aspects of the present invention are as follows [1] to

[15] . [1] A magnetic particle having a core particle, a first coating layer formed on the surface of the core particle, and a second coating layer formed on the surface of the first coating layer, the first coating layer is a crosslinked inorganic layer containing nanomagnetic material; The second coating layer is a polymer layer having a polyethylene glycol group-containing structural unit, and is characterized by having a carboxyl group-containing structural unit. [2] A magnetic particle for immunoassays described in [1], characterized in that the polyethylene glycol group-containing structural unit is a monomer unit having a polyethylene glycol group in a side chain, and the polymer is covalently bonded to the first coating layer. [3] The magnetic particle for immunoassay according to [1] or [2], wherein the polymer has a monomer unit having a carboxyl group on the side chain. [4] A surface of the first coating layer has an area that is not coated with the polymer layer, The magnetic particles for immunoassays according to [2] or [3], characterized in that they have a carboxyl group resulting from a reaction between a hydroxyl group present on the surface of the first coating layer and a carboxylic acid anhydride. [5] The magnetic particle for immunoassay described in [1], characterized in that the polyethylene glycol group-containing structural unit is a surfactant having a polyethylene glycol group, and the polymer has a monomer unit having a carboxyl group in a side chain. [6] The magnetic particle for immunoassay according to [5], wherein the polymer has a monomer unit having a hydrophobic group on the side chain. [7] The magnetic particle for immunoassay according to [5] or [6], characterized in that the surfactant having a polyethylene glycol group is covalently bonded to a polymer. [8] The crosslinked inorganic layer of the first coating layer contains silica. [1] The magnetic particle for immunoassay according to any one of items [1] to [7]. [9] Specific surface area is 2 to 100 m 2 / g. / g.

[10] A method for producing magnetic particles for immunoassays according to any one of [1] to [9], comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a copolymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit and a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution.

[11] A method for producing magnetic particles for immunoassays according to any one of [1] to [9], comprising the following steps (i) to (iv): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer formed thereon in an aqueous solution and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution. (iv) A step of reacting the particles having the polymer layer formed thereon with a carboxylic anhydride to introduce a carboxyl group.

[12] A method for producing magnetic particles for immunoassays according to any one of [1] to [9], comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit in the aqueous solution in the presence of a surfactant having a polyethylene glycol group.

[13] A method for producing magnetic particles for immunoassays according to any one of

[10] to

[12] , further comprising the step (v) of bonding a silane coupling agent having a polymerizable functional group to the surface of the crosslinked inorganic layer between steps (ii) and (iii).

[14] A method for producing magnetic particles for immunoassays according to any one of

[10] to

[13] , characterized in that step (i) includes a step of electrostatically adsorbing a nanomagnetic body to a core particle in an aqueous solution, followed by drying.

[15] A method for producing magnetic particles for immunoassays according to

[14] , characterized in that step (i) comprises a step of dispersing magnetic particles in a high-velocity air stream and dry-processing the surface of the particles by impact force between the particles. Effect of the Invention

[0010] The magnetic particles for immunoassays according to one embodiment of the present invention inhibit the elution of iron and disperse the particles in water. In addition, the particles can carry a large amount of physiologically active substances such as antibodies, enabling highly sensitive immunoassays. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a magnetic particle for immunoassay according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its purpose.

[0013] In the present invention, "immunoassay" refers to a method for measuring the concentration of a physiologically active substance (such as a protein) using an antigen-antibody reaction. A carrier carrying a physiologically active substance such as an antibody or an antigen is used to allow the antigen-antibody reaction to proceed in a container, and the substance is finally visualized by an enzyme reaction. The concentration of an antigen contained in a sample of unknown concentration can be measured by back-calculating from a calibration curve obtained by measuring an antigen of known concentration. Immunoassay methods include the sandwich method, in which an antigen is sandwiched between a first antibody and a second antibody, and the competitive method.

[0014] A magnetic particle for immunoassay according to one embodiment of the present invention is a magnetic particle having a core particle, a first coating layer formed on the surface of the core particle, and a second coating layer formed on the surface of the first coating layer, wherein the magnetic particle has a carboxyl group-containing structural unit, the first coating layer is a crosslinked inorganic layer containing a nanomagnetic material, and the second coating layer is a polymer layer having a polyethylene glycol group-containing structural unit.

[0015] The core particle used in the magnetic particles for immunoassay is a particle located at the very center of the magnetic particles, and there is no particular limitation on the shape or material of the core particle. The shape of the core particle can be appropriately selected, and examples thereof include a spherical shape close to a perfect sphere, a non-spherical shape such as an ellipsoid, a cube, a cylinder, or a polygonal prism, and a particle having a large specific surface area and irregularities such as a porous shape or a particle having protrusions. Since it is suitable for coating many nanomagnetic bodies on the surface of the core particle, a particle having a large specific surface area and irregularities such as a porous shape or a particle having protrusions is preferred.

[0016] In order to obtain magnetic particles with good magnetic response, the particle diameter of the core particles is preferably 0.1 μm or more, more preferably 0.5 μm or more, particularly preferably 1 μm or more, and most preferably 2 μm or more. In order to obtain magnetic particles with good redispersibility in water, the particle diameter of the core particles is preferably 100 μm or less, more preferably 10 μm or less, particularly preferably 5 μm or less, and most preferably 3 μm or less.

[0017] Examples of the material of the core particle include organic compounds such as polymers, inorganic compounds, etc. Examples of the material that can be appropriately selected from these include polymer particles containing styrene-based monomer units, acrylate-based monomer units, or methacrylate-based monomer units, and silica particles.

[0018] Examples of the styrene-based monomer include styrene, α-methylstyrene, vinyltoluene, p-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, 3,4-dimethylstyrene, 4-methoxystyrene, 4-ethoxystyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 2,4-dichlorostyrene, 2,6-dichlorostyrene, 4-chloro-3-methylstyrene, divinylbenzene, and sodium p-styrenesulfonate.

[0019] Examples of the acrylate-based monomer or methacrylate-based monomer include (cyclo)alkyl (meth)acrylates such as (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate; Alkoxy(cyclo)alkyl(meth)acrylates such as 2-methoxyethyl(meth)acrylate and p-methoxycyclohexyl(meth)acrylate; polyvalent(meth)acrylates such as trimethylolpropane tri(meth)acrylate; vinyl esters such as vinyl acetate, vinyl propionate, and vinyl versatate; cyanoacrylates such as 2-cyanoethyl(meth)acrylate, 2-cyanopropyl(meth)acrylate, and 3-cyanopropyl(meth)acrylate; hydroxymethyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxycyclohexyl(meth)acrylate, neopentyl glycol mono(meth)acrylate, Examples of the polymer particles include substituted hydroxy (meth)acrylates such as 3-chloro-2-hydroxypropyl (meth)acrylate and 3-amino-2-hydroxypropyl (meth)acrylate; glycidyl group-containing acrylates such as glycidyl (meth)acrylate, methyl glycidyl methyl acrylate, and epoxidized cyclohexyl (meth)acrylate; and polyfunctional (meth)acrylates such as trimethylolpropane ethoxy triacrylate, pentaerythritol ethoxy tetraacrylate, trimethylolpropane propoxy triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, tricyclodecane dimethanol diacrylate, and ethoxylated phenyl acrylate. The (meth)acrylate may be crosslinked.

[0020] If necessary, the core particles may contain a nanomagnetic material. In addition, a paramagnetic thin film coating layer may be provided on the surface of the core particles. When a paramagnetic coating layer is provided, it is preferable for the thickness to be 0.001 to 1 μm, more preferably 0.001 to 0.1 μm, particularly preferably 0.001 to 0.01 μm, and most preferably 0.001 to 0.005 μm, since it is suitable for reducing residual magnetization of the particles and suppressing aggregation between the particles.

[0021] In addition, as a pretreatment for providing the first coating layer, the surface of the core particle may be coated with a substance having a positive or negative charge. There is no particular limitation on the method for coating the surface of the core particle with a substance having a positive or negative charge, but examples of the method include a method of forming a polymer layer on the surface of the core particle using a monomer having a charge on its side chain, and a method of coating the surface of the core particle with a charged polymer by a layer-by-layer method.

[0022] The first coating layer formed on the surface of the core particle is a crosslinked inorganic layer containing a nanomagnetic material. The nanomagnetic material is a particle having a smaller particle diameter than the core particle, and further has magnetic responsiveness. Since it is preferable that the nanomagnetic material has superparamagnetism, the particle diameter of the nanomagnetic material is preferably 0.001 to 1 μm, more preferably 0.001 to 0.5 μm, particularly preferably 0.001 to 0.1 μm, and most preferably 0.001 to 0.05 μm. An example of the material is iron oxide.

[0023] The nanomagnetic material may contain an inorganic surface modifier such as a lipid or a silane coupling agent on the surface. Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-isocyanatepropyltriethoxysilane.

[0024] The nanomagnetic particles are preferably dispersed in the crosslinked inorganic layer, which allows the surfaces of all the nanomagnetic particles to be uniformly coated with the crosslinked inorganic layer, thereby enhancing the acid resistance of the magnetic particles.

[0025] The content of the nanomagnetic material is preferably 0.1 g / g or more, more preferably 0.2 g / g or more, particularly preferably 0.5 g / g or more, and most preferably 0.7 g / g or more per 1 g of magnetic particles, since it is suitable for making magnetic particles with good magnetic response. Also, since it is suitable for increasing the dispersibility of the magnetic particles in water, the content of the nanomagnetic material is preferably 0.9 g / g or less, more preferably 0.8 g / g or less, particularly preferably 0.7 g / g or less, and most preferably 0.6 g / g or less per 1 g of magnetic particles.

[0026] Furthermore, for the purpose of controlling the specific gravity of the particles for immunoassay and adjusting the sedimentation rate of the particles, the weight proportion of the nanomagnetic material contained in the magnetic particles is preferably 5 to 70 wt%, more preferably 10 to 60 wt%, particularly preferably 15 to 50 wt%, and most preferably 20 to 40 wt%.

[0027] The crosslinked inorganic layer is formed by coating the surface of the core particle with a crosslinked inorganic material. Examples of the crosslinked inorganic material include silica, glass, oxides such as magnesium oxide and alumina oxide, and ceramics such as zirconia and hydroxyapatite. Among these, silica is preferred because it is particularly suitable for increasing acid resistance. By providing a crosslinked inorganic layer, it is possible to increase acid resistance while being hydrophilic, and therefore it is possible to impart the contradictory properties of suppressing iron elution and dispersing the particles in water. In addition, the crosslinked inorganic layer is coated along the shape of the magnetic material on the particle surface and does not completely bury the magnetic material, so that a magnetic particle with a large specific surface area can be obtained, and the amount of biologically active substances such as antibodies carried can be increased. The thickness of the crosslinked inorganic layer is preferably 0.001 μm or more, more preferably 0.005 μm or more, particularly preferably 0.01 μm or more, and most preferably 0.05 μm or more, because it is suitable for increasing acid resistance. In order to obtain magnetic particles with a large specific surface area, the thickness of the crosslinked inorganic layer is preferably 0.1 μm or less, more preferably 0.05 μm or less, particularly preferably 0.02 μm or less, and most preferably 0.01 μm or less.

[0028] Furthermore, for the purpose of controlling the specific gravity of the particles for immunoassay and adjusting the sedimentation rate of the particles, the content of the crosslinked inorganic material contained in the magnetic particles is preferably 0.1 to 10 wt%, more preferably 0.5 to 5 wt%, particularly preferably 1 to 5 wt%, and most preferably 1 to 3 wt%.

[0029] There is no particular limitation on the method for forming the crosslinked inorganic layer containing the nanomagnetic material, but examples include a method in which the nanomagnetic material is adsorbed and accumulated on the surface of the core particle, and then a crosslinked inorganic layer is formed so as to fill the gaps between the nanomagnetic materials, and a method in which the nanomagnetic material is added when forming the crosslinked inorganic layer, etc. The method in which the nanomagnetic material is adsorbed and accumulated on the surface of the core particle, and then a crosslinked inorganic layer is formed so as to fill the gaps between the nanomagnetic materials is preferred because it is easy to control the reaction.

[0030] Examples of the method for adsorbing the nanomagnetic material on the surface of the core particle include a method in which the core particle and a nanomagnetic material having a surface charge opposite to that of the core particle are mixed in an aqueous solution, and the nanomagnetic material is spontaneously adsorbed on the surface of the core particle by electrostatic interaction, a method in which the nanomagnetic material is bonded to the surface of the core particle by a chemical reaction between the functional group on the surface of the core particle and the nanomagnetic material, and a method in which the core particle and the nanomagnetic material are combined by applying mechanical energy. The method for adsorbing the nanomagnetic material on the surface of the core particle may be a combination of a plurality of methods, and for example, the nanomagnetic material may be spontaneously adsorbed on the surface of the core particle by electrostatic interaction, and then the dried particles may be used, and mechanical energy may be applied to firmly adsorb the nanomagnetic material to the core particle.

[0031] As a method for spontaneously adsorbing the nanomagnetic material to the core particle surface by the electrostatic interaction, it is preferable to mix the core particle and the nanomagnetic material in an aqueous solution, which is suitable for increasing the amount of the nanomagnetic material adsorbed to the core particle, and an aqueous solution containing an electrolyte such as sodium chloride is more preferable. In the case of an aqueous solution containing an electrolyte, the electrolyte concentration is preferably such that the nanomagnetic material does not aggregate with each other, and for example, a concentration of about 0.01 to 0.5 M can be suitably used. In addition, in order to firmly fix the adsorbed nanomagnetic material to the core particle surface, it is preferable to dry the particles after compounding in the aqueous solution.

[0032] The method of compounding the core particles and the nanomagnetic material by applying mechanical energy is preferably a method capable of treating particles in a dry manner, such as a device for compounding by swirling force in a high-speed air stream, a device for mixing and stirring using a rotation-revolution mixer or a ball mill, a device for surface coating using a spray dryer, etc. Examples of the device include the Hybridization System NHS Series (manufactured by Nara Machinery Works, Ltd.), Nobilta NOB (manufactured by Hosokawa Micron Corporation), High-Speed ​​Mixing Type Powder Spheroidizer NSM Series (manufactured by Seishin Enterprise Co., Ltd.), and Mini Spray Dryer B-290 Type (Shibata Scientific Co., Ltd.).

[0033] When the compounding is performed by the rotational force in the high-speed airflow, the rotation speed is set to 8000 min-1, which is suitable for firmly fixing the magnetic material to the core particles. -1 More than 9000min is preferable. -1 More preferably, 10,000 min -1 More than 11000min is especially preferable. -1 The above is the most preferable. In addition, a rotation speed of 15,000 min−1 is preferable because it is suitable for forming the particle shape into a spherical shape. -1 Less than 14000min is preferable. -1 Less than 13000min is more preferable. -1 The following is particularly preferred: 12000min -1 The treatment time is preferably 1 to 60 minutes, more preferably 1 to 20 minutes, particularly preferably 1 to 10 minutes, and most preferably 3 to 10 minutes, because it is suitable for forming the particle shape into a spherical shape. The treatment temperature is preferably 25 to 80°C, more preferably 25 to 60°C, particularly preferably 25 to 50°C, and most preferably 25 to 40°C, because it is suitable for suppressing fusion of the particles.

[0034] When silica is formed as a crosslinked inorganic substance, a method of dispersing particles in a solvent and then adding tetraethyl orthosilicate and aqueous ammonia can be suitably used. The amount of tetraethyl orthosilicate added during the reaction is preferably 0.05 g or more per 1 g of particles, more preferably 0.1 g or more, more preferably 0.2 g or more, and most preferably 0.5 g or more, because it is suitable for forming a sufficient amount of silica on the particle surface. In addition, it is preferably 5 g or less per 1 g of particles, more preferably 2 g or less, particularly preferably 1 g or less, and most preferably 0.5 g or less, because it is suitable for suppressing the aggregation of particles during the reaction. In addition, the amount of aqueous ammonia added during the reaction is preferably 20 mL or more per 1 L of solvent, more preferably 30 mL or more, particularly preferably 40 mL or more, and most preferably 50 mL or more, because it is suitable for forming a sufficient amount of silica on the particle surface. Furthermore, since this is suitable for suppressing aggregation of particles during the reaction, the amount is preferably 100 mL or less, more preferably 80 mL or less, particularly preferably 70 mL or less, and most preferably 60 mL or less, per 1 L of solvent.

[0035] As a reaction solvent when forming silica as a crosslinked inorganic material, ethanol, 2-propanol, and butanol are preferable, ethanol or 2-propanol are more preferable, and 2-propanol is particularly preferable, because these are suitable for uniformly coating silica while suppressing particle aggregation.

[0036] The second coating layer formed on the surface of the first coating layer is a polymer layer having a polyethylene glycol group-containing structural unit, and has a carboxyl group-containing structural unit.

[0037] Since particles with a first coating layer formed on the surface of a core particle do not have functional groups for binding biologically active substances such as antibodies to the particles, they cannot support biologically active substances. Therefore, by providing a second coating layer on the surface of a particle provided with a crosslinked inorganic layer, it becomes possible to support antibodies while suppressing non-specific adsorption, and it becomes possible to increase the sensitivity of immunoassays. A carboxyl group-containing structural unit alone has high non-specific adsorption and cannot increase the sensitivity of immunoassays. By having both a carboxyl group-containing structural unit and a polyethylene glycol group-containing structural unit, it becomes possible to increase the sensitivity of immunoassays.

[0038] In one embodiment of the present invention, the polyethylene glycol group-containing structural unit is a component having a polyethylene glycol group, and is preferably a monomer unit having a polyethylene glycol group on the side chain. By being a monomer unit having a polyethylene glycol group on the side chain, a high density polyethylene glycol group can be introduced into the polymer layer on the particle surface, and non-specific adsorption of a physiologically active substance to the particle can be suppressed. Examples of monomers having a polyethylene glycol group include polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, polypropylene glycol monoacrylate, methoxypolyethylene glycol monoacrylate, methoxypolyethylene glycol monomethacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, diethylene glycol monoethyl ether acrylate, diethylene glycol monoethyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate, etc.

[0039] In addition, from the viewpoint of long-term storage stability of the particles, it is preferable that the polymer of the second coating layer is covalently bonded to the first coating layer. There is no particular limitation on the method of covalently bonding the polymer to the first coating layer, but for example, a method of chemically bonding a polymerization initiator or a monomer to the surface of the first coating layer using a silane coupling agent and then carrying out polymerization can be mentioned.

[0040] The polymer of the second coating layer preferably has a monomer unit having a carboxyl group on the side chain. By having a monomer unit having a carboxyl group on the side chain, a physiologically active substance can be immobilized on the particle surface via the carboxyl group, and the sensitivity of the immunoassay can be increased. The monomer having the carboxyl group-containing structural unit is not particularly limited except that it contains a carboxyl group, and examples thereof include acrylic acid, methacrylic acid, maleic acid, and fumaric acid.

[0041] In another embodiment of the present invention, the polyethylene glycol group-containing structural unit is preferably a surfactant having a polyethylene glycol group. By using a surfactant having a polyethylene glycol group, it is possible to introduce a uniform and constant amount of polyethylene glycol groups onto the particle surface, and the production stability of the particles is excellent. Examples of surfactants having a polyethylene glycol group include polyoxyethylene alkyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene myristyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene phenyl ether, polyoxyethylene tribenzyl phenyl ether, polyoxyethylene polyoxypropylene, polyoxyethylene polyoxypropylene alkyl ether, polyethylene glycol alkyl ester, polyoxyalkylene glycol rosin acid ester, polyoxyethylene alkylamine, and polyethylene glycol, and polyoxyethylene alkyl ether having a long chain alkyl having 1 to 20 carbon atoms is preferable. In addition, since it is suitable for suppressing non-specific adsorption, the molecular weight of the polyoxyethylene is preferably 500 or more, preferably 1000 or more, more preferably 1500 or more, and particularly preferably 2000 or more. Furthermore, in order not to inhibit the carrying of a physiologically active substance, the molecular weight of the polyoxyethylene is preferably 20,000 or less, more preferably 10,000 or less, particularly preferably 5,000 or less, and most preferably 3,000 or less.

[0042] Even when a surfactant having a polyethylene glycol group is used as the polyethylene glycol group-containing structural unit, for the same reason as above, it is preferable that the polymer has a monomer unit having a carboxyl group on the side chain. As the monomer having the carboxyl group-containing structural unit, the same monomer as the above-mentioned monomer having a carboxyl group can be suitably used.

[0043] In addition, when a surfactant having a polyethylene glycol group is used as the polyethylene glycol group-containing structural unit, it is preferable that the polymer has a monomer unit having a hydrophobic group on the side chain. By having a monomer unit having a hydrophobic group on the side chain, it is suitable for imparting hydrophobicity for adsorbing or binding an antibody to the particle surface. In addition, by using a monomer having a hydrophobic group on the side chain, it becomes easier to uniformly introduce a surfactant having a polyethylene glycol group onto the particle surface. The monomer unit having a hydrophobic group on the side chain is not particularly limited, but it is preferable that it has a long chain and cyclic alkyl group having 1 to 20 carbon atoms on the side chain, more preferably a long chain and cyclic alkyl group having 1 to 10 carbon atoms on the side chain, particularly preferably a long chain and cyclic alkyl group having 1 to 6 carbon atoms on the side chain, and most preferably a long chain and cyclic alkyl group having 6 carbon atoms on the side chain. Examples of such acrylates include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, t-butyl acrylate, t-butyl methacrylate, n-pentanoyl acrylate, n-pentanoyl methacrylate, n-hexyltyl acrylate, n-hexyl methacrylate, cyclopropyl acrylate, cyclopropyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, phenyl acrylate, phenyl methacrylate, and styrene.

[0044] In addition, it is preferable that the surfactant having a polyethylene glycol group is covalently bonded to a polymer. By covalently bonding the surfactant having a polyethylene glycol group to a polymer, the particles have excellent long-term storage stability. As a method for covalently bonding the surfactant having a polyethylene glycol group to a polymer, a method can be mentioned in which a polymerization reaction is carried out on the particle surface in the presence of a surfactant having a polyethylene glycol group, and the radical generated by the polymerization reaction is chain-transferred to the surfactant having a polyethylene glycol group.

[0045] The second coating layer is formed by either a method of performing polymerization on the particle surface in the presence of a monomer having a polyethylene glycol group in a side chain, or a method of immobilizing a surfactant having a polyethylene glycol group on the particle surface by chemical or physical interaction. Examples of the method of immobilizing a surfactant having a polyethylene glycol group on the particle surface by chemical or physical interaction include a method of performing polymerization on the particle surface in the presence of a surfactant having a polyethylene glycol group, and a method of physically adsorbing a surfactant having a polyethylene glycol group on the particle surface.

[0046] In addition, the second coating layer may contain a hydroxyl group-containing structural unit as a hydrophilic group other than polyethylene glycol, and examples of the monomer include hydroxyethyl acrylate, hydroxyethyl methacrylate, N-(2-hydroxyethyl)acrylamide, 2-hydroxyphenyl acrylate, 2-hydroxyphenyl methacrylate, 3-hydroxyphenyl acrylate, 3-hydroxyphenyl methacrylate, 4-hydroxyphenyl acrylate, and 4-hydroxyphenyl methacrylate.

[0047] The carboxyl group-containing structural unit can be introduced into the polymer by copolymerizing a monomer having a polyethylene glycol group-containing structural unit with a monomer having a carboxyl group-containing structural unit. Alternatively, the carboxyl group-containing structural unit may be introduced (modified) into the polymer layer by reacting a carboxylic acid anhydride with a particle having a polymer layer having a polyethylene glycol group-containing structural unit. Alternatively, the carboxyl group-containing structural unit may be introduced into the polymer layer by reacting with a functional group present on the surface of the crosslinked inorganic layer. Examples of the carboxylic acid anhydride include acetic anhydride, propionic anhydride, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, and benzoic anhydride.

[0048] The polymerization initiator used in forming the second coating layer is not particularly limited, and depending on the desired polymerization temperature and polymerization rate, azo compounds such as azobisisobutyronitrile, peroxides such as potassium peroxodisulfate, peroxyesters such as Perhexyl PV and Perbutyl O (manufactured by NOF Corporation), and the like can be suitably used.

[0049] The polymer layer, which is the second coating layer, is preferably chemically bonded to the first coating layer directly or via a linker. By being chemically bonded directly or via a linker, acid resistance and solvent resistance can be improved. The presence of chemical bonds can be confirmed by the fact that the polymer does not disappear even when washed with a solvent that dissolves the polymer. If there is no chemical bond, the coated polymer will almost entirely dissolve and disappear.

[0050] The second coating layer is fixed to the first coating layer by chemical bonding, which is suitable for enhancing the acid resistance and solvent resistance of the magnetic particles, so it is preferable that the crosslinked inorganic layer has a silane coupling agent having a polymerizable functional group (and residue) on the surface. Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0051] When the silane coupling agent is reacted on the surface of the crosslinked inorganic layer, a method of adding the silane coupling agent and aqueous ammonia after dispersing the particles in a solvent can be suitably used. The amount of the silane coupling agent added during the reaction is preferably 0.05 g or more per 1 g of particles, more preferably 0.1 g or more, more preferably 0.2 g or more, and most preferably 0.5 g or more, because it is suitable for reacting a sufficient amount of the silane coupling agent on the particle surface. In addition, it is preferably 5 g or less per 1 g of particles, more preferably 2 g or less, particularly preferably 1 g or less, and most preferably 0.5 g or less, because it is suitable for suppressing the aggregation of particles during the reaction. Furthermore, the amount of aqueous ammonia added during the reaction is preferably 20 mL or more per 1 L of solvent, more preferably 30 mL or more, particularly preferably 40 mL or more, and most preferably 50 mL or more, because it is suitable for reacting a sufficient amount of the silane coupling agent on the particle surface. Furthermore, since this is suitable for suppressing aggregation of particles during the reaction, the amount is preferably 100 mL or less, more preferably 80 mL or less, particularly preferably 70 mL or less, and most preferably 60 mL or less, per 1 L of solvent. As a reaction solvent for reacting the silane coupling agent, since it is suitable for reacting the silane coupling agent uniformly while suppressing particle aggregation, alcohols such as methanol, ethanol, 2-propanol, butanol, etc. are preferable, methanol, ethanol, and 2-propanol are more preferable, and methanol or 2-propanol is particularly preferable.

[0052] The amount of polymer coated in the second coating layer is not particularly limited, but since it is suitable for producing magnetic particles with a large specific surface area, the amount of polymer coated per 1 g of magnetic particles is preferably 1 g / g or less, more preferably 0.5 g / g or less, particularly preferably 0.1 g / g or less, and most preferably 0.05 g / g or less. Also, since it is suitable for improving acid resistance, the amount of polymer coated per 1 g of magnetic particles is preferably 0.001 g / g or more, more preferably 0.01 g / g or more, particularly preferably 0.1 g / g or more, and most preferably 0.5 g / g or more. The amount of polymer coated can be measured by measuring the TG-DTA of the particles before and after coating with the polymer and determining the difference in thermal weight loss before and after coating with the polymer. It can also be calculated by determining the thickness of the polymer from a scanning electron microscope image of the particle cross section or a transmission electron microscope image of the particle. The amount of carboxyl groups in the magnetic particles is preferably 5 μmol / g or more, more preferably 10 μmol / g or more, particularly preferably 20 μmol / g or more, and most preferably 50 μmol / g or more, per 1 g of magnetic particles, since it is suitable for making the magnetic particles capable of binding many antibodies. In addition, the amount of carboxyl groups in the magnetic particles is preferably 200 μmol / g or less, more preferably 100 μmol / g or less, particularly preferably 50 μmol / g or less, and most preferably 20 μmol / g or less, per 1 g of magnetic particles, since it is suitable for suppressing non-specific adsorption of substances other than antibodies to the magnetic particles and generation of measurement noise in immunoassays. The method for measuring the amount of carboxyl groups includes a method of mixing pyrenyldiazomethane with magnetic particles and quantifying the amount of pyrenyldiazomethane lost by the reaction, or a method of directly quantifying the amount of carboxyl groups on the surface of the magnetic particles by potentiometric titration.

[0053] The magnetic particles for immunoassay according to one embodiment of the present invention have a specific surface area of ​​2 m 2 / g or more. 2 / g or more, the amount of antibody that can be bound to the surface of the magnetic particles per unit weight can be increased, and the signal strength in immunoassays can be increased. 2 / g or more is more preferable, 2 / g or more is particularly preferable, and 10m 2 On the other hand, a specific surface area of ​​100 m / g or more is preferable because it is suitable for increasing the mechanical strength of the magnetic particles. 2 / g or less is preferable, and 50m 2 / g or less is more preferable, and 30m 2 / g or less is particularly preferable, and 20m 2 / g or less is most preferable.

[0054] The magnetic particles for immunoassay according to one embodiment of the present invention can be obtained by a production method including the following steps (i) to (iii). (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a random copolymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit and a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution. It can also be obtained by a production method including the following steps (i) to (iv). (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution and forming a copolymer layer on the surface of the particles by free radical polymerization of a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution. (iv) A step of reacting the particles having the copolymer layer formed thereon with a carboxylic anhydride to introduce a carboxyl group. It can also be obtained by a production method including the following steps (i) to (iii). (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit in the aqueous solution in the presence of a surfactant having a polyethylene glycol group. In step (i), the nanomagnetic material is physically adsorbed to the surface of the core particle by a method of contacting the nanomagnetic material having an opposite charge to the surface charge of the core particle, a method of contacting the hydrophobic nanomagnetic material with the hydrophobic core particle, or a method of contacting the nanomagnetic material with the paramagnetic core particle. The method of contacting the core particle and the nanomagnetic material is not particularly limited, and it can be done by stirring in a liquid phase or a gas phase. Since it is suitable for uniformly adsorbing the nanomagnetic material to the core particle, it is preferable to electrostatically adsorb the nanomagnetic material to the core particle in an aqueous solution. In addition, in order to firmly fix the electrostatically adsorbed nanomagnetic material, it is preferable to dry the particles after electrostatic adsorption. Furthermore, since it is suitable for making the shape of the particles spherical, it is preferable to disperse the magnetic particles in a high-speed airflow and perform surface modification in a dry manner by the impact force between the particles.

[0055] In step (ii), a crosslinked inorganic layer is formed on the surface of the particles to which the nanomagnetic material has been adsorbed in step (i). There is no particular limitation on the method for forming the crosslinked inorganic layer, but examples include a method in which the particles are dispersed in a solution containing a reagent and a reaction catalyst that are raw materials for the crosslinked inorganic layer, and a crosslinked inorganic layer is formed on the particle surface by proceeding with a reaction, and a method in which the particle surface is coated with the crosslinked inorganic layer or the raw materials thereof.

[0056] In step (iii), the particles on which the crosslinked inorganic layer was formed in step (ii) are dispersed in an aqueous solution, and a monomer having a carboxyl group-containing structural unit and a monomer having a polyethylene glycol group-containing structural unit are subjected to free radical polymerization in the aqueous solution to form a copolymer layer on the surface of the particles. Examples of the polymerization method include a dispersion polymerization method in which polymerization is performed in a state in which all components other than the particles are dissolved in a solvent, and a seed polymerization method in which polymerization is performed in a state in which a monomer incompatible with the solvent is used and the monomer is adsorbed on the particles. In addition, the seed polymerization method can be appropriately selected from soap-free polymerization that does not use an emulsifier and emulsion polymerization that uses an emulsifier. In addition, peroxides, azo compounds, etc. can be used as a radical generating source, and the solubility in the solvent or monomer can be appropriately selected.

[0057] Alternatively, in step (iii), a monomer having a polyethylene glycol group-containing structural unit may be subjected to free radical polymerization to form a polymer layer, and then in step (iv), a carboxylic anhydride may be reacted to introduce a carboxyl group onto the particle surface. The method for reacting the particle surface with the carboxylic anhydride is not particularly limited, and can be achieved by dispersing the particles in a solvent not containing water and adding an excess amount of the carboxylic anhydride.

[0058] Furthermore, between steps (ii) and (iii), a step (v) of bonding a silane coupling agent having a polymerizable functional group to the surface of the crosslinked inorganic layer may be included. The method of bonding a silane coupling agent to the surface of the crosslinked inorganic layer is not particularly limited, and can be selected from a method of dispersing particles in a solvent and adding a silane coupling agent, and a method of coating the particle surface with a silane coupling agent. In addition, an acidic or basic aqueous solution serving as a reaction catalyst may be used in combination as necessary.

[0059] In addition, in step (iii), instead of using a monomer having a polyethylene glycol group-containing structural unit, a polymer containing a polyethylene glycol group may be used, and the polyethylene glycol group-containing structural unit may be introduced into the particles by fixation via chemical bonding to the particle surface due to radical chain transfer during polymerization, or by fixation via physical adsorption to the particle surface due to either hydrophobic interaction or electrostatic interaction with the particles, or the entanglement effect with the molecular chains on the particle surface.

[0060] The magnetic particles for immunoassay according to one embodiment of the present invention can be used in an immunoassay device by immobilizing an antibody on the surface of the particles. The antibody is preferably bound via a carboxyl group on the particle surface, for example, by activating the carboxyl group by reacting it with a condensing agent such as carbodiimide, and then reacting the activated carboxyl group with an amino group of the antibody. EXAMPLES

[0061] The present invention will be described in detail below with reference to the embodiments for carrying out the present invention. However, these are merely examples for explaining the present invention, and are not intended to limit the present invention to the following contents. Furthermore, the present invention can be practiced with appropriate modifications within the scope of the gist of the present invention. Unless otherwise specified, commercially available reagents were used. [Measurement of polymer coating amount] The particles before and after the polymer coating were subjected to TG-DTA measurement to determine the thermal weight loss from 100° C. to 560° C. The amount of polymer coating was determined by assuming that the thermal weight loss of the particles before the polymer coating was ΔTG1 and the thermal weight loss of the particles after the polymer coating was ΔTG2, and ΔTG2-ΔTG1 was the amount of polymer coating. [Measurement of carboxyl group amount] 2 mL of ethyl acetate was added to 10 mg of magnetic particles and stirred at room temperature for 20 minutes. 2 mL of ethyl acetate in which 0.12 mg of pyrenyldiazomethane had been dissolved was added to this particle dispersion and stirred at room temperature for 50 minutes. After removing the particles, the supernatant was diluted 10 times with methanol and the absorbance at 392 nm was measured. This absorbance was designated as A1, and the absorbance of the solution obtained by carrying out the same procedure without using particles was designated as A0. The amount of carboxyl groups was calculated using the following formula.

[0062] 138×(A0-A1)μmol / g [Evaluation of water dispersibility] 0.1 g of the dried powdered magnetic particles was added to 10 g of ion-exchanged water, and the mixture was shaken by hand to perform the evaluation. ○: Uniformly dispersible in water ×: Not dispersible in water [Measurement of specific surface area] Measurements were performed using a multipoint BET method using nitrogen gas as the adsorption gas, using QUADRASOR Bevo, a product of Quantachrome Co. [Evaluation of iron ion elution] 10 mg of magnetic particles were added to 1 mL of pH 3.5 citrate buffer and stirred for 17 hours at 37° C. The solution from which the particles had been removed was used as the measurement sample, and the amount of leached iron ions was evaluated by measuring the absorbance of the solution at a wavelength of 460 nm. [Preparation of diluted solid phase suspension and labeled antibody solution for detection] An excess amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to magnetic particles dispersed in MES buffer (pH 6.0) and incubated at 37°C for 1 hour. Anti-thyroid stimulating hormone (TSH) antibody was added in citrate buffer (pH 3.5) and incubated at 37°C for 3 hours to bind the anti-TSH antibody to the magnetic particles. Next, the magnetic particles were blocked by incubation for 17 hours in Tris-HCl buffer (pH 8.0) containing a non-specific adsorption inhibitor consisting of polyethylene glycol, to obtain anti-TSH antibody-immobilized magnetic particles (A). (A) was further diluted with MES buffer (pH 6.0) containing 8% collagen peptide to prepare a diluted solid phase suspension (B). The conjugate of anti-TSH antibody and alkaline phosphatase was also diluted with MES buffer (pH 6.2) containing 5% bovine serum albumin to prepare a labeled antibody solution for detection (C). [Preparation of samples for evaluation of non-specific binding (NSB) and posicount] A 0.03 mol / L Tris-HCl buffer (pH 8.0) containing 5% collagen peptide was prepared and used as the NSB evaluation sample (D). In addition, TSH was added to a 0.03 mol / L Tris-HCl buffer (pH 8.0) containing 5% collagen peptide to use as the posicount evaluation sample (E). [NSB and posicount measurements, sensitivity evaluation] NSB and Posicount were measured using a measurement reagent (a freeze-dried product containing a diluted solid-phase suspension (B) and a labeled antibody solution for detection (C)) and sensitivity was evaluated.

[0063] The NSB was measured according to the following procedure.

[0064] The lyophilized diluted solid suspension (B) was dissolved in pure water containing Triton X-100 and the NSB evaluation sample (D), and then the immunoreaction was carried out at 37°C for 5 minutes, and the first B / F separation was performed. Next, a detection labeled antibody solution (C) dissolved in pure water containing Triton X-100 was added, and the immunoreaction was carried out at 37°C for 3 minutes, and the second B / F separation was performed. Then, a chemiluminescence substrate for alkaline phosphatase (DIFURAT, 3-(5-tert-butyl-4,4-dimethyl-2,6,7-trioxabicyclo[3,2,0]hept-1-yl)phenyl phosphate disodium salt) and a chemiluminescence auxiliary reagent containing fluorescein were added, and the luminescence intensity (count / sec (cps)) was measured and used as the NSB value.

[0065] The posicount was measured according to the following procedure.

[0066] The lyophilized diluted solid suspension (B) was dissolved in pure water containing Triton X-100 and a sample for positive count evaluation (E), and then subjected to an immunoreaction at 37°C for 5 minutes, and the first B / F separation was performed. Next, a detection labeled antibody solution (C) dissolved in pure water containing Triton X-100 was added, and the immunoreaction was performed at 37°C for 3 minutes, and the second B / F separation was performed. Then, a chemiluminescence substrate for alkaline phosphatase (DIFURAT, 3-(5-tert-butyl-4,4-dimethyl-2,6,7-trioxabicyclo[3,2,0]hept-1-yl)phenyl phosphate disodium salt) and a chemiluminescence auxiliary reagent containing fluorescein were added, and the luminescence intensity (count / sec (cps)) was measured and used as the positive count value.

[0067] Sensitivity was evaluated by calculating the ratio of posicount value / NSB value. [Example 1] Step (i) (Preparation of magnetized fine particles) 5.0 g of polydivinylbenzene particles (particle diameter 2.5 μm), 1.2 g of polyvinylpyrrolidone, and 6 mL of 1N-hydrochloric acid aqueous solution were dispersed in 160 mL of pure water at a rotation speed of 180 rpm. After heating to 80 ° C under a nitrogen atmosphere, 6 g of urea, 2 g of iron (II) chloride tetrahydrate, and 3 g of iron (III) chloride hexahydrate were added and reacted for 5 hours. After separating the particles and the reaction solution by filtering this particle dispersion, the particles were dispersed again in 200 mL of pure water at a rotation speed of 180 rpm. After heating to 80 ° C under a nitrogen atmosphere, 0.2 N-sodium hydroxide aqueous solution was dropped and reacted for 15 hours. After washing with pure water, 5.75 g of particles coated with iron oxide were obtained.

[0068] 1 g of the obtained iron oxide-coated particles was dispersed in 50 mL of pure water at room temperature at a rotation speed of 100 rpm. 1.0 g of a magnetic material (material: magnetite, particle size: 10 nm, product name: EMG607, manufactured by Ferrotec Corporation) having a cationic dispersant on the surface was added to this particle dispersion liquid, and the mixture was reacted at room temperature at a rotation speed of 100 rpm for 2 hours. The particles were washed with pure water and further dried at 50°C for 15 hours to obtain 1.93 g of magnetized particles.

[0069] Step (ii) (Silica Coating on Magnetized Particles) 1 g of the magnetized microparticles was dispersed in 400 mL of ethanol, 3 g of tetraethyl orthosilicate was added, and the mixture was stirred at room temperature at 300 rpm. 21 g of 25% aqueous ammonia was added, and the mixture was reacted at 35°C and 300 rpm for 4 hours. The mixture was washed with pure water and ethanol, and dried under reduced pressure. The thickness of the silica layer confirmed by a transmission electron microscope was about 20 nm.

[0070] Step (v) (Introduction of methacryl groups into silica-coated particles) 1 g of the silica-coated particles was dispersed in 75 mL of methanol, 0.5 g of 3-methacryloxypropyltrimethoxysilane and 15 g of 25% aqueous ammonia were added, and the mixture was reacted at 60° C. and 300 rpm for 3 hours. The mixture was washed with methanol and pure water, and dried under reduced pressure.

[0071] Step (iii) (Polymer Coating on Methacrylic Group-Introduced Particles) 0.1 g of the particles with methacrylic groups introduced therein was dispersed in 18 mL of pure water, and 0.038 g of polyethylene glycol methyl ether acrylate (Mn=300), 0.008 g of sodium styrenesulfonate, and 0.02 g of potassium persulfate were added. After degassing, the mixture was reacted for 3 hours at 65° C. in a nitrogen atmosphere. The mixture was washed with pure water and methanol, and dried under reduced pressure.

[0072] Step (iv) (Introduction of a carboxyl group) 0.1 g of the polymer-coated particles was dispersed in 2 mL of tetrahydrofuran, and 0.1 g of succinic anhydride and 0.01 g of dimethylaminopyridine were added thereto, followed by reaction at 65° C. for 2 hours. (Evaluation Results) The polymer coating amount was 0.006 g / g, and the amount of carboxyl groups was 44 μmol / g.

[0073] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. The specific surface area was 38 m 2 The specific surface area was large, with a specific surface area of ​​1.0 μm / g. In addition, the NSB was 76, the positive count was 1,065,800, and the sensitivity was 14,024, showing excellent sensitivity. [Example 2] Particles were prepared in the same manner as in Example 1, except that a mixture of polyethylene glycol methyl ether acrylate (Mn=300) and methacrylic acid in a weight ratio of 75:25 was used as the monomer in step (iii) of Example 1 instead of polyethylene glycol methyl ether acrylate (Mn=300). (Evaluation Results) The polymer coating amount was 0.008 g / g, and the amount of carboxyl groups was 58 μmol / g.

[0074] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. In addition, the NSB was 34, the posicount was 422,700, and the sensitivity was 12,432, showing excellent sensitivity. [Example 3] Particles were prepared in the same manner as in Example 1, except that a mixture of polyethylene glycol methyl ether acrylate (Mn=300) and acrylic acid in a weight ratio of 75:25 was used as the monomer in step (iii) of Example 1 instead of polyethylene glycol methyl ether acrylate (Mn=300), and step (iv) after polymer coating was not performed at all. (Evaluation Results) The amount of the polymer coated was 0.012 g / g, and the amount of the carboxyl group was 50 μmol / g.

[0075] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. In addition, the NSB was 56, the posicount was 592,300, and the sensitivity was 10,577, showing excellent sensitivity. [Example 4] Instead of step (iii) in Example 1, polymer coating was performed by the following method, and step (iv) after polymer coating was not performed at all. Otherwise, particles were produced in the same manner as in Example 1. (Polymer coating on methacrylic group-introduced particles) 0.2 g of the particles having methacrylic groups introduced therein obtained in step (v) of Example 1 was dispersed in 6 mL of pure water, and 0.03 g of polyoxyethylene (47) lauryl ether, 0.015 g of methacrylic acid, 0.04 g of cyclohexyl methacrylate, and 0.004 g of "Perbutyl O" (product name: NOF Corp.) were added thereto, and after degassing, the mixture was reacted at 80° C. for 8 hours under a nitrogen atmosphere. The mixture was washed with pure water and methanol, and dried under reduced pressure. (Evaluation Results) The polymer coating amount was 0.169 g / g, and the amount of carboxyl groups was 30 μmol / g.

[0076] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. The specific surface area was 6.3 m 2 The specific surface area was large, with a specific surface area of ​​0.01 mm / g. In addition, the NSB was 41, the positive count was 558,800, and the sensitivity was 13,629, showing excellent sensitivity. [Example 5] The procedure of Example 4 was repeated except that cyclohexyl methacrylate was not added in step (iii) (polymer coating on methacrylic group-introduced particles). (Evaluation Results) The polymer coating amount was 0.025 g / g, and the amount of carboxyl groups was 69 μmol / g.

[0077] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. In addition, the NSB was 48, the posicount was 526397, and the sensitivity was 10967, showing excellent sensitivity. [Example 6] Step (i) (Preparation of magnetized fine particles) 1 g of polydivinylbenzene particles (particle diameter 2.2 μm) was dispersed in 50 mL of 0.1 M sodium chloride pure water at room temperature at a rotation speed of 100 rpm. 1.2 g of a magnetic material (material: magnetite, particle diameter: 10 nm, product name: EMG607, manufactured by Ferrotec Corporation) having a cationic dispersant on the surface was added to this particle dispersion liquid, and the reaction was carried out at room temperature at a rotation speed of 100 rpm for 2 hours. The mixture was washed with pure water and further dried at 50°C for 15 hours to obtain 2.18 g of magnetized particles. The magnetized particles were placed in a hybridization system NHS-0 (manufactured by Nara Machinery Co., Ltd.) and rotated at a speed of 11,300 min. -1 The treatment was performed for 5 minutes at an average temperature of 35°C.

[0078] Step (ii) (Silica Coating on Magnetized Particles) 1 g of the magnetized microparticles was dispersed in 10 mL of 2-propanol, 0.5 g of tetraethyl orthosilicate was added, and the mixture was stirred at room temperature at 180 rpm. 0.5 mL of 25% aqueous ammonia was added, and the mixture was reacted at 35°C at 180 rpm for 4 hours. The mixture was washed with methanol and dried under reduced pressure. The thickness of the silica layer confirmed by a transmission electron microscope was about 10 nm.

[0079] Step (v) (Introduction of methacryl groups into silica-coated particles) 1 g of the silica-coated particles was dispersed in 10 mL of methanol, 0.5 g of 3-methacryloxypropyltrimethoxysilane and 0.5 mL of 25% aqueous ammonia were added, and the mixture was reacted at 35° C. and 180 rpm for 3 hours. The mixture was washed with methanol and pure water, and dried under reduced pressure.

[0080] Step (iii) (Polymer Coating on Methacrylic Group-Introduced Particles) 1 g of the particles having methacrylic groups introduced therein was dispersed in 10 mL of pure water in which 0.3 g of polyoxyethylene (47) lauryl ether had been dissolved, and 0.07 g of methacrylic acid, 0.05 g of cyclohexyl methacrylate, and 0.005 g of NOF Corp.'s product name "Perbutyl O" were added, and the mixture was stirred at room temperature at 180 rpm for 1 hour, degassed, and then reacted at 80° C. for 2 hours under a nitrogen atmosphere. The mixture was washed with pure water and methanol, and dried under reduced pressure. (Evaluation Results) The polymer coating amount was 0.05 g / g.

[0081] The magnetic particles produced had excellent water dispersibility and little leaching of iron ions. In addition, the NSB was 36, the posicount was 803081, and the sensitivity was 22308, showing excellent sensitivity. [Comparative Example 1] Particles were prepared in the same manner as in Example 1, except that none of the steps (ii), (v), (iii), and (iv) of Example 1 were performed. (Evaluation Results) The magnetic particles thus produced had poor water dispersibility and leached out a large amount of iron ions. [Comparative Example 2] Instead of carrying out any of steps (ii), (v), (iii), and (iv) of Example 1, the magnetic particles were modified with an organic silane coupling agent by the following method. The rest of the procedure was the same as in Example 1 to prepare the particles. (Modification of magnetic particles with organic silane coupling agents) 1 g of the magnetized microparticles obtained in step (i) of Example 1 was dispersed in 75 mL of methanol. 0.5 g of 3-methacryloxypropyltrimethoxysilane and 15 g of 25% aqueous ammonia were added, and the mixture was reacted at 60° C. and 300 rpm for 3 hours. The mixture was washed with methanol and pure water, and dried under reduced pressure. (Evaluation Results) The magnetic particles thus produced had poor dispersibility in water and leached out a large amount of iron ions. [Comparative Example 3] Instead of carrying out any of steps (ii), (v), and (iv) of Example 1, the magnetized particles were coated with a polymer by the following method. Particles were produced in the same manner as in Example 1 except for the above. (Polymer Coating on Magnetized Particles) 0.1 g of the magnetized particles obtained in step (i) of Example 1 was dispersed in 18 mL of pure water, 4 g of methyl methacrylate and 0.02 g of potassium persulfate were added, and after degassing, the mixture was reacted for 3 hours at 65° C. in a nitrogen atmosphere. The mixture was washed with pure water and methanol and dried under reduced pressure. (Evaluation Results) The particles produced had poor dispersibility in water. The specific surface area was 1.8 m 2 / g, and the specific surface area was small. [Comparative Example 4] Particles were prepared in the same manner as in Example 1, except that the steps (ii), (v), and (iv) of Example 1 were not performed. (Evaluation Results) The produced particles had a large amount of iron ions dissolved out. [Comparative Example 5] Particles were prepared in the same manner as in Example 1, except that steps (v), (iii), and (iv) in Example 1 were not performed. (Evaluation Results) The magnetic particles thus produced had an NSB of 70, a positive count of 139,986, and a sensitivity of 2,000, which was poor in sensitivity. [Comparative Example 6] Particles were prepared in the same manner as in Example 1, except that the step (iii) in Example 1 was not carried out. (Evaluation Results) The magnetic particles thus produced had an NSB of 365, a positive count of 962124, and a sensitivity of 2636, which was poor in sensitivity. [Comparative Example 7] The procedure of Example 4 was repeated except that polyoxyethylene (47) lauryl ether was not added in step (iii) of Example 4 (polymer coating of methacrylic group-introduced particles). (Evaluation Results) The polymer coating amount was 0.057 g / g, and the amount of carboxyl groups was 68 μmol / g.

[0082] The magnetic particles thus produced had an NSB of 526, a positive count of 971,801, and a sensitivity of 1,848, which was poor in sensitivity. [Comparative Example 8] The procedure of Example 4 was repeated except that polyoxyethylene (47) lauryl ether and cyclohexyl methacrylate were not added in step (iii) of Example 4 (polymer coating of methacrylic group-introduced particles). (Evaluation Results) The amount of the polymer coating was below the detection limit, and the amount of carboxyl groups was 67 μmol / g.

[0083] The magnetic particles thus produced had an NSB of 392, a positive count of 863,384, and a sensitivity of 2,203, which was poor in sensitivity. [Comparative Example 9] The same procedures as in Example 4 were carried out except that methacrylic acid was not added in step (iii) (coating the methacrylic group-introduced particles with a polymer). (Evaluation Results) The polymer coating amount was 0.066 g / g.

[0084] The magnetic particles produced had an NSB of 127, a positive count of 769571, and a sensitivity of 6060, which was poor in sensitivity.

[0085] [Table 1] [Explanation of symbols]

[0086] 1. Core Particle 2 Nanomagnetic materials 3 Crosslinked inorganic layer 4. Polymer layer having hydrophilic group-containing structural unit

Claims

1. A magnetic particle having a core particle, a first coating layer formed on a surface of the core particle, and a second coating layer formed on a surface of the first coating layer, the first coating layer is a crosslinked inorganic layer containing nanomagnetic material; the second coating layer is a polymer layer that is a layer of a polymer having a polyethylene glycol group-containing structural unit, and has a carboxyl group-containing structural unit; The magnetic particles for immunoassay, wherein the polymer is covalently bonded to the surface of the first coating layer via a silane coupling agent.

2. 2. The magnetic particle for immunoassay according to claim 1, wherein the polyethylene glycol group-containing structural unit is a monomer unit having a polyethylene glycol group on a side chain.

3. 3. The magnetic particle for immunoassay according to claim 1, wherein the polymer has a monomer unit having a carboxyl group on a side chain.

4. A magnetic particle for immunoassays as described in claim 2 or 3, characterized in that the surface of the first coating layer has an area that is not covered with the polymer layer and has a carboxyl group derived from a reaction between a hydroxyl group present on the surface of the first coating layer and a carboxylic acid anhydride.

5. 2. The magnetic particle for immunoassay according to claim 1, wherein the polyethylene glycol group-containing structural unit is a surfactant having a polyethylene glycol group, and the polymer has a monomer unit having a carboxyl group on a side chain.

6. 6. The magnetic particle for immunoassay according to claim 5, wherein the polymer has a monomer unit having a hydrophobic group on a side chain.

7. 7. The magnetic particle for immunoassay according to claim 5, wherein the surfactant having a polyethylene glycol group is covalently bonded to a polymer.

8. 8. The magnetic particle for immunoassay according to claim 1, wherein the cross-linked inorganic layer of the first coating layer contains silica.

9. Specific surface area is 2 to 100 m 2 The magnetic particles for immunoassay according to any one of claims 1 to 8, wherein the magnetic particle has a molecular weight of 1 / g.

10. A method for producing magnetic particles for immunoassays according to any one of claims 1 to 9, comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a copolymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit and a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution.

11. A method for producing magnetic particles for immunoassays according to any one of claims 1 to 9, comprising the following steps (i) to (iv): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) a step of dispersing the particles having the crosslinked inorganic layer formed thereon in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer having a polyethylene glycol group-containing structural unit in the aqueous solution. (iv) A step of reacting the particles having the polymer layer formed thereon with a carboxylic anhydride to introduce a carboxyl group.

12. A method for producing magnetic particles for immunoassays according to any one of claims 1 to 9, comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer having a carboxyl group-containing structural unit in the aqueous solution in the presence of a surfactant having a polyethylene glycol group.

13. The method for producing magnetic particles for immunoassays according to any one of claims 10 to 12, further comprising the step (v) of binding a silane coupling agent having a polymerizable functional group to the surface of the crosslinked inorganic layer between steps (ii) and (iii).

14. The method for producing magnetic particles for immunoassays according to any one of claims 10 to 13, characterized in that step (i) comprises a step of electrostatically adsorbing a nanomagnetic material to a core particle in an aqueous solution, followed by drying.

15. The method for producing magnetic particles for immunoassays according to any one of claims 10 to 13, characterized in that step (i) comprises a step of dry surface modification by impact force between particles while dispersing the magnetic particles in a high-velocity airflow.

Citation Information

Patent Citations

  • Magnetic particle and immunoassay using same

    JP1991115862A

  • Virus detection method

    JP2004141116A

  • Method for manufacturing particle for diagnostic product

    JP2004205481A

  • Magnetic particle for immunological examination

    JP2006226689A

  • Magnetic particle for immunological examination

    JP2006226690A